KAJIAN TERHADAP PEMANFAATAN HUTAN MANGROVE OLEH MASYARAKAT (STUDI KASUS DESA TANAH MERAH, KECAMATAN KUPANG TENGAH, KABUPATEN KUPANG) - Christanty Wahyuni Selan; Paulus Un; Nixon Rammang (Wana Lestari, 2021)
The results showed that the community understands the importance of the role of mangrove forests in people's lives so that in its utilization, the community maintains the preservation of mangrove forests by replanting mangrove saplings and maintaining the cleanliness of the area around the mangrove forest. Based on the results of the research, the business of selling commodities from mangrove forests provides a relative benefit to the community around the mangrove forest with the highest amount of revenue for shrimp commodity, namely Rp. 2,545,920,000 per year and the lowest revenue of Rp. 250,560,000 per year. After analyzing the mangrove forest commodity sales with an average R / C ratio of 19> 1, the selling of mangrove forest products in Tanah Merah Village is profitable.